Engineered nano scale formulation strategies to augment efficiency of nutraceuticals. (November 2019) - Ali, Asad; Ahmad, Usama; Akhtar, Juber; Badruddeen,; Khan, Mohd Muazzam
Graphical abstract: Highlights: Nutraceuticals provide essential components to the body and prevent disease. Nutraceuticals have limited aqueous solubility and bioavailability. Nanotechnology ensures better efficiency of nutraceuticals than the traditional products. Encapsulation of bioactives prevent them from g.i.t degradation. Release of nutraceuticals is enhanced when delivered in nano sized form. Abstract: Nutraceuticals have been widely explored for promoting health outcomes and in management of various diseases. They are considered to be neutral and safe and are extensively used to promote overall health. They play a vital role in modifying and maintaining normal body physiological functions. However, the bioactives present in nutraceuticals are unable to achieve their potential outcomes due to limited aqueous solubility leading to poor bioavailability profile and interaction with gastro-intestinal fluids. Majority of conventional products in market are unable to show their therapeutic outcome. Nanotechnology has tremendous potential to revolutionize the nutraceutical market. Recent progress in field of nutraceutical delivery has incorporated nanotechnology to overcome the drawbacks accompanying nutraceuticals. This review focuses on issues associated with nutraceuticals and various nanoscale formulation approaches like liposomes, nanoemulsions, nanocrystals, lipid and polymeric nanoparticles to obtain an insight to recent developments in nutraceuticals segment.